Factors Influencing Online Shopping Attitude and Impulsive Buying among Generation Z in U.P West, India - Kant, Tushar; Chaturvedi, Umesh Kumar (Airlangga Journal of Innovation Management, 2026)
The rapid growth of digital technology has transformed consumer buying behavior, resulting in increased impulsive purchasing within the e-commerce environment. Even though impulsive buying has been widely studied, only partial experiential research has integrated various psychological and technological drivers into a single theoretical framework, specifically for Generation Z consumers in the emerging country of U.P. West, India. This study fills this gap and uses the Stimulus-Organism-response framework to investigate how digital stimuli impact online impulsive buying through the mediating part of shopping attitude. The quantitative research design was followed, and data from Generation Z consumers in the UP- West region of India were collected using a structured questionnaire and cluster sampling. Confirmatory Factor Analysis, Exploratory Factor Analysis, and Structural Equation Modelling with IBM SPSS and AMOS were used to analyze the data. The outcomes indicate that stimulus factors are significant and positively influence online shopping attitude, which in turn drives online impulsive buying behavior. The study covers the applications of the S-O-R framework to the Indian Generation Z context and provides applied visions for e-marketers to propose appealing, reliable, and emotionally appealing online shopping environments.